Gender differences in attitudes towards psychological help-seeking among chinese medical students: a comparative analysis - Lei Qiu; Hengyi Xu; Yingqi Li; Yonghui Zhao; Qin Yang (BMC, 2024)
Abstract Background Medical students are known to be at a greater risk of psychological disorders compared to the general population. However, their rate of help-seeking behavior is low. The purpose of this study was to explore the influencing factors of attitudes towards psychological help-seeking among Chinese medical students and to examine its gender differences. Methods A total of 3,453 medical students from three medical colleges in Hainan Province, China, completed anonymous questionnaires that included socio-demographic attributes, the Family APGAR Index, the General Health Questionnaire (GHQ-20), and the Attitudes Towards Seeking Professional Psychological Help Short Form (ATSPPH-SF). Associations between predictor variables and attitudes towards help-seeking were explored using multivariate linear regression, and regression models with interaction terms were employed to test gender difference. Results The mean score on ATSPPH-SF Scale was 15.04 ± 3.45, with males scoring significantly lower than females (14.34 vs. 15.64, P < 0.0001). For both male and female groups, psych knowledge, mental health status, family function and help-seeking utility perception significantly influenced attitudes toward psychological help-seeking. Furthermore, having more than once psycho-help experiences was positively correlated with women's attitudes. Significant interactions were found between gender and mental health status. Conclusion Attitude towards seeking psychological help was relatively negative among Chinese medical students. The implementation of interventions should take into account the at-risk population, especially the males and individuals with poor mental health.